2021
DOI: 10.5005/jp-journals-10006-1855
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Institutional Isolation Measures on Postnatal Women in Level 3 COVID Facility in Northern India

Abstract: Aim:The COVID-19 pandemic has influenced many aspects of a woman's life. The aim of the present study was to explore whether hospital isolation and containment policies among women giving birth in COVID-19 Level 3 facility enhanced psycho-emotional distress in the immediate postpartum period. Methodology: The study was designed as an observational study. All women giving birth at Santosh Hospital, a Level 3 COVID facility in Ghaziabad, from June 2020 to October 2020, were studied. Data collection was done by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Additionally, with the restriction of postpartum visitors, many mothers were eager to discharge and reunite with their partner and family [55] , [83] , but others perceived the rushed discharge as negligence and poor quality of care [44] , [54] , [71] . Moreover, a longer postpartum hospital stay during COVID was associated with higher postpartum depression scores [84] .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, with the restriction of postpartum visitors, many mothers were eager to discharge and reunite with their partner and family [55] , [83] , but others perceived the rushed discharge as negligence and poor quality of care [44] , [54] , [71] . Moreover, a longer postpartum hospital stay during COVID was associated with higher postpartum depression scores [84] .…”
Section: Resultsmentioning
confidence: 93%
“…In Ciagran et al’s study [31] , 73.2% of mothers did not perceive the pandemic restrictions to have affected their relationship with their baby. A small percentage of mothers (3.6% to 17.7%) were separated from their babies immediately after birth [67] , [70] , [85] which is associated with lower birth satisfaction [67] and higher risk of postnatal depression [84] .…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the social networks, the inability to connect to the family (Gupta et al, 2021 ), a low number of network members seen in person, and a higher proportion of relatives (Myers & Emmott, 2021 ) were associated with a heightened risk of PPD. Besides, the number of household members were found to be protecting mothers against PPD (Matsushima et al, 2021 ; Miranda et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from that, the increase in non-exclusive breastfeeding, such as increased use of formula milk or practiced complementary and formula breastfeeding had heightened the risk of PPD among postpartum women (Fallon et al, 2021 ; Miranda et al, 2021 ; Zanardo et al, 2021a , 2021b ). Furthermore, women with a previous history of pregnancy or postnatal complications are also more depressed (Gupta et al, 2021 ). Nevertheless, studies also found no significant difference in PPD risk between mothers with or without postnatal complications (An et al, 2021 ; Matsushima et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation